IgE Reactivity to Common Cypress (C. Sempervirens) Pollen Extracts: Evidence for Novel Allergens - Youcef. Shahali, MSc; Jean-Pierre Sutra, PhD; Gabriel. Peltre, PhD; Denis. Charpin, MD; Hélène Sénéchal, PhD; Pascal. Poncet, PhD (World Allergy Organization Journal, 2010)
Background Cypress pollen is becoming an increasing cause of respiratory allergy in some regions worldwide.Objective The aim of this study was to determine some of the main allergens implicated in the common cypress (C. sempervirens) pollen allergy.Methods Pollen extracts were optimized by using some detergents and chaotropes in order to solubilize both water and non-water soluble proteins. C. sempervirens pollen extracts were resolved by one and two dimensional electrophoresis and assayed with sera of allergic subjects.Results Five predominant allergens with apparent molecular masses ranging from 14 to 94 kDa were detected. Two principal IgE-binding patterns were clearly distinguishable: a first one represents patients with a heterogeneous IgE reactivity to several allergens (pI 3.5-8.5) with molecular masses ranging from 35 to 94 kDa (HMW). The second one corresponds to little less than 50 percent of tested patients with specific IgE binding to 2-3 spots (pI 10-11) of about 14 kDa and weak or no reactivity to HMW allergens.Conclusion The extraction of water insoluble proteins allows the revelation of novel allergens as well as different allergen sensitization patterns in the C. sempervirens pollen allergy. These novel IgE reactive components may subsequently be applied to expand the panel of well-defined cypress pollen molecules for a more efficient allergen-based diagnosis and therapy. Keywords: C. sempervirens, cypress pollen, water insoluble allergens, immunoblotting patterns